Overview of SERPING1 Variations Identified in Hungarian Patients With Hereditary Angioedema - Szabó, Edina; Csuka, Dorottya; Andrási, Noémi; Varga, Lilian; Farkas, Henriette; Szilágyi, Ágnes (Frontiers in Allergy, 2022)
Background Hereditary angioedema (HAE) due to C1-inhibitor (C1-INH) deficiency (C1-INH-HAE) is a rare autosomal dominant disorder, characterized by recurrent, unpredictable edematous symptoms involving subcutaneous, and/or submucosal tissue. C1-INH-HAE may be caused by more than 700 different mutations in the gene encoding C1-INH (SERPING1) that may lead to decreased protein synthesis or to functional deficiency. Methods Concentrations of C1-INH, C4, C1q, and anti-C1-INH antibodies, as well as functional C1-INH activity were determined in subjects suffering from edematous symptoms and admitted to the Hungarian Angioedema Center of Reference and Excellence. In those patients, who were diagnosed with C1-INH-HAE based on the complement measurements, SERPING1 was screened by bidirectional sequencing following PCR amplification and multiplex ligation-dependent probe amplification. For detecting large deletions, long-range PCRs covering the entire SERPING1 gene by targeting 2–7 kb long regions were applied. Results Altogether 197 individuals with C1-INH deficiency belonging to 68 families were identified. By applying Sanger sequencing or copy number determination of SERPING1 exons, 48 different mutations were detected in 66/68 families: 5 large and 15 small insertions/deletions/delins, 16 missense, 6 nonsense, and 6 intronic splice site mutations. Two novel variations (p.Tyr199Ser [c.596A>C] and the duplication of exon 7) were shown to cosegregate with deficient C1-inhibitor level and activity, while two other variations were detected in single patients (c.797_800delinsCTTGGAGCTCAAGAACTTGGAGCT and c.812dup). A series of long PCRs was applied in the remaining 2 families without an identified mutation and a new, 2606 bp long deletion including the last 91 bp of exon 6 (c.939_1029+2515del) was identified in all affected members of one pedigree. In the remaining one family, a deep intronic SERPING1 variation (c.1029+384A>G) was detected by a targeted next-generation sequencing panel as reported previously. Conclusions Sequencing and copy number determination of SERPING1 exons uncover most pathogenic variants in C1-INH-HAE patients, and further methods are worth to be applied in cases with unrevealed genetic background. Since knowledge of the genetic background may support the establishment of the correct and early diagnosis of C1-INH-HAE, identification of causative mutations and reporting data supporting the interpretation on the pathogenicity of these variants is of utmost importance.